PENGARUH PERSEPSI HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA UD.AUDYKA SUPPLY & SERVICE (ASS) - Nusabika, Awdiqit Dwi; Herdinata, Christian; Padmawidjaja, Liestya (Universitas Ciputra Surabaya, 2023)
The growth of food commodities and basic necessities has experienced positive growth every year, this is also triggered by the increase in population growth in Indonesia. The existence of this positive phenomenon becomes a good opportunity for similar business actors, especially in the object of this research, namely UD.Audyka Supply & Service (ASS). UD.ASS was established in 2011 in Sumbawa Besar, West Nusa Tenggara, which is a business engaged in the distribution of basic food and secondary crops. There is a problem phenomenon of decreasing sales turnover of UD.ASS every year, and there are criticisms and suggestions from customers regarding price and location perceptions. So this study aims to analyze the effect of price perception, and location on purchasing decisions at UD.ASS. The research method used in this research is quantitative, with multiple linear regression. The research sample was 104 respondents. Data was collected using hypothesis testing and statistical tests. The results of this study are the perception of price and location on the purchasing decision of UD.ASS.